Implementing Emancipated Curriculum in English Language Learning: Teachers’ Perspectives - Albar, Muhammad Alqowiy; Ilma, Ridha; Okta Sukma, Fitri Alya (ENGLISH FRANCA : Academic Journal of English Language and Education, 2025)
This study explored teachers' perceptions of implementing the Emancipated Curriculum in English language learning at a private junior high school in Palembang. A qualitative case study design was used, involving two English teachers selected through total sampling. Data were collected through semi-structured interviews focusing on indicators such as teachers' views on the curriculum's implementation, benefits, and limitations. The data were transcribed and analyzed thematically to identify patterns and categories related to teachers' experiences. To ensure accuracy, member checking was conducted by sharing transcripts and findings with participants for validation. The results showed that teachers perceived the curriculum positively for its flexibility, student-centered approach, and opportunities for creative instruction. Project-based and differentiated learning were considered effective in encouraging student engagement and autonomy. However, teachers faced challenges, including limited training, reduced English teaching hours, and difficulties accessing relevant learning materials. These findings suggest that the successful implementation of the Emancipated Curriculum depends on strong institutional support, ongoing professional development, and sufficient resources to help teachers apply innovative approaches effectively.